Job loss and household labor supply adjustments in developing countries: evidence from Argentina - Ciaschi, Matías (2020)
Using longitudinal data for Argentina, this paper measures the labor supply reaction of different household members to a breadwinner’s job loss. Firm events and local unemployment shocks are exploited as exogenous sources of variation to estimate the causal effect. Our main findings show that job loss by the male household head has a significant and substantial effect on the labor supply response of other household members, both at the extensive and intensive margin. While we do not find any effect on daughters, female partners and sons increase their labor market participation. The latter are also more likely to drop out from the educational system. These results are stronger among economically vulnerable households.